PENGARUH PELATIHAN SMALL-SIDED GAMES TERHADAP KEMAMPUAN DRIBBLING SISWA SEPAKBOLA SISWA SMPN 4 KLARI - Fauzi, Dira; Simarmata, Daniel Pernando; Susianti, Evi; Afrinaldy, Rolly (JUARA : Jurnal Olahraga, 2024)
The purpose of this study was to determine the effect of small side games training method on dribbling ability in students participating in extracurricular football SMPN 4 Klari. This research uses a quantitative approach with experimental research methods. In this study there was a population of 36 students with a sample of 31 students. The samples used were students participating in extracurricular football at SMPN 4 Klari class VII and VIII. The sampling technique used is purposive sampling. The instrument used in this study was the Short Dribbling Test (Bangsbo & Mohr, 2012: 99). Data analysis techniques use t-test, namely by comparing pretest results with posttest in the experimental group. Based on the results of research that has been obtained by data analysis and hypothesis testing from the average before treatment and after treatment, there has been a significant improvement in small side games training methods on the dribbling ability of students participating in extracurricular football SMPN 4 Klari. When viewed from the average pretest of 19.35 and the average posttest of 18.51, a mean difference of 0.83 was obtained which showed that the small side games training method on the dribbling ability of students participating in extracurricular football SMPN 4 Klari showed a change of 4.48% better than before training.